2016
DOI: 10.1016/j.adro.2016.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Use of mobile device technology to continuously collect patient-reported symptoms during radiation therapy for head and neck cancer: A prospective feasibility study

Abstract: PurposeAccurate assessment of toxicity allows for timely delivery of supportive measures during radiation therapy for head and neck cancer. The current paradigm requires weekly evaluation of patients by a provider. The purpose of this study is to evaluate the feasibility of monitoring patient reported symptoms via mobile devices.Methods and materialsWe developed a mobile application for patients to report symptoms in 5 domains using validated questions. Patients were asked to report symptoms using a mobile dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 13 publications
1
38
0
1
Order By: Relevance
“…Additional work must be done to improve clinician satisfaction, and to determine the system’s usefulness and its optimal incorporation into clinical practice. Electronic methods of capturing PROs have also been reported in the inpatient setting, and in the use of mobile devices [14, 18]. Further research should focus on the utility of these interventions in assessing patient recovery after major gynecologic surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Additional work must be done to improve clinician satisfaction, and to determine the system’s usefulness and its optimal incorporation into clinical practice. Electronic methods of capturing PROs have also been reported in the inpatient setting, and in the use of mobile devices [14, 18]. Further research should focus on the utility of these interventions in assessing patient recovery after major gynecologic surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Mixed findings may be because of high study heterogeneity in terms of remote monitoring methodology, patient‐provider communication, and the patient population. Remote monitoring methodology has included study‐initiated calls from an automated telephone system, 79 patient‐initiated calls to an automated telephone system, 77,80,84 study‐initiated online questionnaires, 24,81 patient‐initiated smartphone‐based or online questionnaires, 82,86 study‐initiated telephone calls from a nurse or nurse practitioner, 83,85 study‐initiated calls from a research coordinator, 87 or a paper symptom diary 78 . Some studies incorporated automated alerts about severe or worsening symptoms to providers, 77,79,80,82,84,88 whereas others encouraged patients to discuss symptoms with their providers 78 .…”
Section: The Evidence Base For Clinical Monitoring Of Pghdmentioning
confidence: 99%
“…Taken together, these data suggest that thoughtfully designed remote symptom monitoring interventions may improve outcomes in patients with cancer. In addition, numerous studies have shown that remote symptom monitoring is feasible and acceptable to patients and providers 80,84,86,88‐93 . However, more work is clearly needed to identify characteristics of health systems, patient populations, and intervention designs to ensure that remote symptom monitoring is maximally efficacious 94,95 …”
Section: The Evidence Base For Clinical Monitoring Of Pghdmentioning
confidence: 99%
“…PALM: In the Blum et al (2014) study, 49% of the 84 participants preferred the PALM (handheld computer) to the paper-based assessment. Several studies reported high patient acceptability and feasibility regarding the electronic assessment of symptoms (Abernethy et al, 2008;Andikyan et al, 2012;Basch et al, 2007;Blum et al, 2014;Chan et al, 2011;Falchook et al, 2016;Wintner et al, 2015;Wolpin et al, 2008;Wu et al, 2016). Three studies (Head et al, 2009;Mirkovic, Kaufman, & Ruland, 2014;Ruland, Maffei, et al, 2013) considered the usability and usefulness of a device from the patient's perspective.…”
Section: Touchscreen Computerized Survey Assessing Psychosocial Well-mentioning
confidence: 99%